Adaptive FEM for NURBS Surface Shells. Issue 1 (October 2016) - Weise, Michael
Abstract: The application of shell theories in the finite element method (FEM) requires a description of the shell midsurface geometry and its derivatives. Modern computer aided design software uses non‐uniform rational B‐splines (NURBS) for geometry description. We give some insights on how to implement adaptive FEM for NURBS surface Naghdi shells. A speciality is the incorporation of tangential vectors with continuous directions, but jumping lengths. Such vectors may occur when NURBS surfaces are combined. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)